Current research trends on cognition, integrative complexity, and decision-making: a systematic literature review using activity theory and neuroscience - Molina, Isaac; Molina-Perez, Edmundo; Sobrino, Fernanda; Tellez-Rojas, Mario Arturo; Zamora-Maldonado, Hilda C.; Plaza-Ferreira, María; Orozco, Yessica; Espinoza-Juarez, Victor; Serra-Barragán, Luis; De Unanue, Adolfo (Frontiers in Psychology, 2023)
Introduction This article presents a systematic literature review that follows the PRISMA and PICOS guidelines to analyze current research trends on cognition, integrative complexity (IC) (a cognitive feature focusing on information processing in a person’s response rather than its quantity or quality), and decision-making from the perspectives of activity theory and neuroscience. Methods The study examines 31 papers published between 2012 and 2022 and 19 articles specifically related to neuroscience. We performed a content analysis using six categories within activity theory: subjects, objects, rules, community, division of labor, and outcomes. Results The study investigates the relationship between decision-making outcomes and IC as a cognitive feature in various contexts. Additionally, content analysis on neuroscience and IC revealed significant research gaps, including understanding the nature of IC, challenges related to its measurement, and differentiation from other cognitive features. We also identify opportunities for investigating the brain’s activity during decision-making in relation to IC. Discussion We address the need for a more precise categorization of IC in studies of cognition, IC, and decision-making. We discuss the implications of our analysis for understanding the cognitive nature of IC and the potential of neuroscience methods for studying this attribute.